PENELITIAN PENAMBAHAN BAHAN SERBUK DOLOMITE DAN PASIR BRANTAS PADA CAMPURAN ASPAL BETON - Faisal Abdul Yusuf; Ahmad Ridwan; Yosef Cahyo Setianto Poernomo (Faculty of Engineering, Kadiri University, 2019)
Asphalt Concrete (Hotmix) is a mixture of coarse aggregate, fine aggregate, and filler (filler) with asphalt binder in high-temperature conditions (heat) with a composition that is examined and regulated by technical specifications. In this research, concrete asphalt mixture was added with dolomite powder as a mixture in filler to be an alternative material for portland cement filler mixture to minimize the price of portal and cement, which is increasingly expensive, and brantas sand as fine aggregate to study and determine the effect of dolomite powder and brantas sand in the mixture asphalt concrete with the addition of levels of 5%, 10%, and 15%. From the results of the study obtained the value of adding dolomite powder with levels of 5%, 10%, 15% at VIM values of 11.99%, 15.28%, 10.29 , VMA value of 26.30%, 29.05%, 24.88%, VFB value of 54.49%, 48.33%, 58.81%, stability value of 3402.503 kg, 3294.030 kg, 1958.946 kg, MQ value 733,8130 kg, 456,1891 kg, 471,9089 kg and from the testing chart the optimum content is at levels 5.5% to 8% and the maximum level is at 5% level.Aspal Beton (Hotmix) adalah campuran agregat kasar, agregat halus, dan bahan pengisi (Filler) dengan bahan pengikat aspal dalam kondisi suhu tinggi (panas) dengan komposisi yang diteliti dan diatur oleh spesifikasi teknis. Pada penelitian ini, campuran aspal beton diberi bahan tambahan serbuk dolomite sebagai campuran pada filler agar menjadi bahan alternativ campuran filler semen portaland untuk meminimalisir harga semen portaland yang semakin mahal dan pasir brantas sebagai agregat halus untuk mempelajari dan mengetahui pengaruh serbuk dolomit dan pasir brantas pada campuran aspal beton dengan penambahan kadar 5%, 10%, dan 15%.dari hasil penelitian didapat nilai penambahan serbuk dolomite dengan kadar 5%, 10%, 15% pada nilai VIM sebesar 11,99%, 15,28%, 10,29, nilai VMA 26,30%, 29,05%, 24,88%, nilai VFB 54,49%, 48,33%, 58,81%, nilai stabilitas 3402,503 kg, 3294,030 kg, 1958,946 kg, nilai MQ 733,8130 kg, 456,1891 kg, 471,9089 kg dan dari grafik pengujian kadar optimum pada kadar 5,5% sampai 8% dan kadar maximum pada kadar 5%.